Spooling and bending of composite pipes - Chan, Ko Zun (2014)
This report aims to study the flexural response of composite pipes which are stored on large spools for ease of storage, handling and installation. Experimental techniques were utilized to examine the bending behavior and identify the minimum spooling radius of a pipe before yielding occurs. 4-point bending tests were implemented to simulate spooling conditions whereby a pipe is loaded until failure. Experiments were conducted on various material systems and lay-ups to assess its influence on the spoolability of composite pipes. The load-strain and moment-curvature response obtained from the 4-point bending tests were used in parallel to determine the minimum spooling radius without inducing damage in the composite pipe during storage. In conjunction to the 4-point bending tests, compression and torsion tests were also conducted to determine the stiffness properties of the pipes such as the elastic and shear moduli respectively.